Comparing load balancing algorithms for web application in cloud environment - Zakaria Benlalia; Karim Abouelmehdi; Abderrahim Beni-hssane; Abdellah Ezzati (Institute of Advanced Engineering and Science, 2020)
Cloud computing has emerged as a new paradigm for providing on-demand computing resources and outsourcing software and hardware infrastructures. Load balancing is one of the major concerns in cloud computing environment means how to distribute load efficiently among all the nodes. For solving such a problem, we need some load balancing algorithms, so in this paper we will compare the existing algorithms for web application.and based on results obtained we choose the best among them.